The 61st Brazilian Ceramic Conference : selected, peer reviewed papers from the 61st Brazilian Ceramic Conference, June 4-7 2017, Gramado, Brazil - Muccillo, Eliana Navarro Santos (Trans Tech Publications Ltd, 2019)
This volume of the journal contains articles which were presented on the 61st Brazilian Ceramic Congress, which was held from June 4th to 7th 2017 in Gramado, Brazil. These publications contain the research results in the area of the synthesis, processing, and characterization of ceramic, ceramic-based materials and composites, biomaterials and technologies of building materials production and waste processing in construction. Ceramics, Clay, Composites, Bentonite, Concrete, Biomaterials, Construction Waste Materials Science, Building Materials, Bioscience and Medicine.